Mobile money, market transactions, and household income in rural Kenya - Enoch M. Kikulwe; Elisabeth Fischer; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2013)
Mobile phone based money services have spread rapidly in many developing countries. We analyze micro level impacts using panel data from smallholder farmers in Kenya. Mobile money use has a large positive net impact on household income. One important pathway is through remittances, which contribute to income directly but also help to reduce risk and liquidity constraints, thus promoting agricultural commercialization. Mobile money users apply more purchased inputs, market a larger proportion of their output, and have higher farm profits. These results suggest that mobile money can help to overcome some of the important market access constraints of smallholder farmers.
Keywords: D13; O13; O16; O33; Q12; 330; mobile banking; remittances; market transactions; agriculture; Africa; Kenya